2011
DOI: 10.1039/c1ib00113b
|View full text |Cite
|
Sign up to set email alerts
|

Spatially organized in vitro models instruct asymmetric stem cell differentiation

Abstract: Understanding developmental biology requires knowledge of both the environmental factors regulating stem cell differentiation, which are increasingly being defined, and their spatial organization within a structurally heterogeneous niche, which is still largely unknown. Here we introduce spatially organized stem cell developmental models to interrogate the role of space in fate specification. Specifically, we developed Differential Environmental Spatial Patterning (δESP) to organize different microenvironments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…Additionally, patterning approaches have demonstrated the ability to create complex co-culture platforms, and thereby may inform approaches to spatially control differentiation. For example, the differentiation of ESCs in co-culture with spatially defined monolayers comprising both extraembryonic endoderm and trophoblast stem cells, which resemble extraembryonic microenvironments, successfully recapitulated proximal-distal patterning by directing divergent ESC fate specification [32]. …”
Section: Stem Cell-derived Factor Manipulationmentioning
confidence: 99%
“…Additionally, patterning approaches have demonstrated the ability to create complex co-culture platforms, and thereby may inform approaches to spatially control differentiation. For example, the differentiation of ESCs in co-culture with spatially defined monolayers comprising both extraembryonic endoderm and trophoblast stem cells, which resemble extraembryonic microenvironments, successfully recapitulated proximal-distal patterning by directing divergent ESC fate specification [32]. …”
Section: Stem Cell-derived Factor Manipulationmentioning
confidence: 99%
“…Bio-flip chip (BFC) cell patterning creates patterns by overturning a cell-loaded microwell array onto a recipient substrate, whereupon the cells fall out of the well and onto the recipient substrate while maintaining their arrangement (62). This technique has been combined with stenciling to pattern mESCs along with other cell populations found in the blastocyst to create developmental models to study early embryonic patterning events in vitro (63) (Figure 3G). Other microscale approaches to control organization include flowing droplet arrays consisting of multiple cell types, which have been used to create controlled co-cultures in small media volumes (64), and laminated microfluidic flows to modulate cell soluble signaling versus contact-mediated signaling (65), a technique that could be applied to stem cells.…”
Section: Microfluidic Approaches To Study Cell-secreted Signalingmentioning
confidence: 99%
“…(G) Combined stencil and BFC patterning. Stencil patterning of trophoblast stem cells (TS, green) and extra-embryonic endoderm cells (XEN, red) combined with BFC patterning of mESCs in a co-culture resembling the organization of the blastocyst induces polarized differentiation (Wnt3 staining) similar to AP polarity (63). Reproduced by permission of the Royal Society of Chemistry.…”
Section: Summary Pointsmentioning
confidence: 99%
“…Recent studies have demonstrated the ability to direct the differentiation of ESCs by exogenous administration of molecules known to be involved in cell fate determination 3, 9, 10 . Nevertheless, robust and reliable spatial organization of the 3D environment in EBs is typically difficult to achieve 6, 11 . In order to generate fused multicellular 3D-aggregates in a repeatable manner, there is a significant need for a high-content engineering tool that simultaneously allows for direct visualization and phenotype analysis of individual multicellular aggregates.…”
Section: Introductionmentioning
confidence: 99%